Variabilidade da produção de frutos de abobrinha italiana em função do manejo - Carpes, Ricardo Howes (2006)
In order to determine the variability for the culture of Italian pumpkin with passing of the multiple harvests in protecting environment and verifying the influence of the plants that had not presented apt fruits to be harvested in definitive harvest in its variance in different handling one conducted a work in the stations winter-spring and summer-autumn 2004/2005, in pertaining area to the Department of Fitotecnia, in UFSM, SantaMaria, RS. The experiment consisted in two tunnels with different handlings, three lines of twenty and three meters length of twenty and five plants in each. The pants had been being for the plastic greenhouse with spacing of 0,80 m between plants and 1,0 m between lines. Had been carried the harvests of the fruits with length 18 cm. Applied the test of Bartlett between the six variances of the lines of culture of each harvest and, it between the average variances of the six to verify the homogeneity between harvests in each station of culture. For comparison of the averages of production of each line of culture, in each harvest inside of each tunnel, and between lines of culture, with the same position in the tunnels test t in the first work was applied. Variances and averages oscillate of significant form between the lines of culture with passing of the productive cycle and of the multiple carried through, independent harvests of the station of culture, and still, they tend to be significantly different between the culture lines, when in climatic conditions of limitation. In as the work, the test of Bartlett was applied to verify the homogeneity enters the variances of each plant, for the situations where had been considered the all plants of the line of culture and for only with the harvested plants, in each type of irrigation, the two stations of culture. In the cases where the behavior of the variances was presented as heterogeneous, new tests of Bartlett between the variances had been become fulfilled, grouping the multiple successive harvests. The system of irrigation for dripping compared with the one for aspersion presented behavior of bigger heterogeneous between the variances. With the methodology of considering value zero, in the plants without fruits harvested in determined harvest, the heterogeneous between the variances tends to increase.